From memory to prospection: what are the overlapping and the distinct components between remembering and imagining? - Zheng, Huimin; Luo, Jiayi; Yu, Rongjun (Frontiers in Psychology, 2014)
Reflecting on past events and reflecting on future events are two fundamentally different processes, each traveling in the opposite direction of the other through conceptual time. But what we are able to imagine seems to be constrained by what we have previously experienced, suggesting a close link between memory and prospection. Recent theories suggest that recalling the past lies at the core of imagining and planning for the future. The existence of this link is supported by evidence gathered from neuroimaging, lesion, and developmental studies. Yet it is not clear exactly how the novel episodes people construct in their sense of the future develop out of their historical memories. There must be intermediary processes that utilize memory as a basis on which to generate future oriented thinking. Here, we review studies on goal-directed processing, associative learning, cognitive control, and creativity and link them with research on prospection. We suggest that memory cooperates with additional functions like goal-directed learning to construct and simulate novel events, especially self-referential events. The coupling between memory-related hippocampus and other brain regions may underlie such memory-based prospection. Abnormalities in this constructive process may contribute to mental disorders such as schizophrenia.